PENGARUH RASIO MOLAR DAN WAKTU REAKSI TERHADAP HASIL DAN MUTU BIODISEL MELALUI REAKSI TRANSESTERIFIKASI DENGAN GELOMBANG ULTRASONIK - Viffit Desiyana; Agus Haryanto; Sri Hidayati (The University of Lampung, 2014)
Biodiesel is alkyl esters that are produced through alcoholysis or (transesterification) process of triglycerides with methanol or ethanol in the presence of bases. The purpose of this study was to determine the effect of the molar ratio and reaction time on the yield and quality of biodiesel from used cooking oil through transesterification process assisted ultrasonic wave at a frequency of 42 kHz. This research was conducted using waste cooking oil obtained from the cracker factory in Sukarame, Bandar Lampung. The chemicals used are methanol and NaOH as catalyst (both are of technical grade).The experiment was arranged by two factors, namely the molar ratio and reaction time. Factor molar ratio of methanol the used cooking oil is composed of three levels, namely 3 : 1, 4,5 : 1, and 6 : 1. Reaction time factor consists of three levels, 5 minutes, 10 minutes, and 30 minutes. All treatments are carried out with three replications. The results showed that the presence of ultrasonic wave can eliminate the process of heating and stirring at conventional biodiesel transesterification process. Production of biodiesel produced in this reaction ranged from 55,67 to 70,67 % with the characteristics density of 0,86 to 0,94 kg/liter, acid number 0,09 to 0,15 %, and viscosity of 4,16 to 8,07 cSt. Statistically, molar ratio and reaction time significantly affect the yield and acid number of biodiesel but did not significantly affected the viscosity and density of biodiesel. Molar ratio and reaction time best obtained at a molar ratio of 6 : 1 with reaction time of 30 minutes. Biodiesel produced could potentially be used as a substitute fuelin kerosene stove. Keywords: Molar ratio, reaction time, biodiesel, used cooking oil, ultrasonic wave